Nano-herbicides a sustainable strategy for weed control - Konathala Kusumavathi; Sachin Kanta Rautaray; Smritikana Sarkar; Subhaprada Dash; Tapas Ranjan Sahoo; Susanta Kumar Swain; Debadatta Sethi (Plant Nano Biology)
In agriculture, nanotechnology has seen remarkable advancements, particularly with the development of nanotechnology-enabled materials for weed management. Nano-herbicides, which are herbicides formulated through nanotechnology, are created using inorganic, organic, or hybrid (organic-inorganic) components. Nano-herbicides can control metal ions and organic chemicals in agricultural settings, thanks to their compact size and high specific surface area. Studies have shown that nano-herbicides may offer improved weed control compared to non-nano formulations. However, research on their mode of action on plants and their potential environmental risks is still in its early stages. Therefore, further studies are essential to ensure the safe use of nano-herbicides for environmental preservation and human health. This paper provides an overview of the current state of nano-enabled herbicides, highlighting design strategies for creating nanostructures specifically engineered for weed control. It also critically examines the behavior and impact of nano-herbicides on plants, aiming to develop products that promote sustainable, environmentally-friendly agricultural practices.